Warm and slightly reduced mantle under the off-rift Snæfellsnes Volcanic Zone, Iceland - Meer, Quinten H. A. van der; Bali, Enikő; Guðmundur H. Guðfinnsson; Kahl, Maren; Rasmussen, Maja B. (Journal of petrology, 2021)
Olivine (Fo75-91) with spinel inclusions (Cr# 10-61) in basaltic lavas/tephras from the off-rift Snæfellsnes Volcanic Zone in Iceland record the chemistry, temperature and oxygen fugacity of fractionating magmas. After a detailed assessment of equilibrium conditions, crystallization temperatures and oxygen fugacity can be calculated from the composition of homogeneous Cr-spinel and Al-chromite inclusions in olivine phenocrysts. Geologically meaningful results can occasionally be obtained when homogenous spinel is enclosed in mildly zoned olivine and KDMg-Fe [(Mg/Fe)olivine/(Mg/Fe2+)spinel] is within the range for homogenous spinel in homogeneous olivine (3.5-4.3 for our samples). Spinel in normal zoned Fo84.7-90.9 olivine records the primitive stages of magma fractionation and has crystallized from clinopyroxene-free primitive melts, probably at Moho depth and/or below. Discrepancies between Tol-liq (Mg-Fe2+ diffusion sensitive) and TAL (diffusion insensitive) suggest that some primitive olivines experienced magma mixing, completely overprinting their Fo content. Consequentially, Tol-liq in primitive olivines occasionally records residence rather than crystallization conditions. Temperature (1187-1317°C) gradually decreases across normal zoned Fo84.7-90.9 olivine and controls fO2 (Δlog fO2 (QFM) −0.6 ± 0.2). Recharge-related primitive Fo83.8-86.8 mantles of reverse zoned olivine contain the most primitive Cr-spinel linked to crustal magma storage zones. These spinels are mostly antecrysts with high Cr# (41.1-47.9) similar to spinel in normal zoned olivines that were captured by olivine and equilibrated in terms of Mg-Fe2+. A rare olivine macrocryst crystallized alongside clinopyroxene (wehrlite) and includes abundant homogeneous Al-rich Cr-spinels. These are unique because they appear to record closed-system fractional crystallization rather than magma mixing and because they show that Cr-poor, Al-rich spinel crystallized alongside clinopyroxene. The macrocryst olivine-spinel pairs record lower crustal crystal mush conditions with fO2 around the QFM buffer and Tol-liq of ∼1200°C, similar to recharge-related mantles of reverse zoned olivine. More evolved compositions occur in the cores of reverse zoned olivine (Fo75-85) that contain Cr-spinel, Fe-spinel and Al-magnetite. Contrary to spinel in more primitive olivine, these compositions are diverse and follow increasing 100Fe3+/(Cr+Al+Fe3+) of 12.3 to 54.8 and TiO2 (3.3 to 14.7 wt %) at decreasing Mg# (57.4 to 24.1) and Cr# (30.4 to 9.9) and rapidly increasing oxygen fugacities (Δlog fO2 (QFM) +0.2 to +2.0) over only a limited temperature decrease (Tol-liq: 1190 to 1145°C). These compositions span the ‘spinel gap’ and are extremely rare globally. Their preservation is probably related to high-temperature crystallization followed by rapid cooling. These compositions occur at two of the four investigated volcanic centres (Búðahraun and Berserkjahraun) and indicate a strong influence of crustal magmatic processes on crystal composition and fO2, which is absent in the other two locations (Ólafsvíkurenni and Nykurhraun). Spinel and olivine compositions support the tectonically controlled decompression melting of a fertile peridotitic source at elevated mantle temperatures relative to MORB and more reducing conditions than other off-rift magmatism in Iceland.
Gesehen am 14.04.2022